2013
DOI: 10.1371/journal.pone.0068568
|View full text |Cite
|
Sign up to set email alerts
|

Relapse Rate and Associated-Factor of Recurrence after Stopping NUCs Therapy with Different Prolonged Consolidation Therapy in HBeAg Positive CHB Patients

Abstract: BackgroundMany chronic hepatitis B (CHB) patients recur after off-therapy and have to accept prolonged consolidation therapy with NUCs. We investigated the rate of HBV relapse after stopping NUCs therapy with different time period of prolonged consolidation therapy in HBeAg positive CHB patients, and analyzed the associated-factor of recurrence.MethodsWe recruited 162 HBeAg-positive CHB patients who met the standard of stopping NUCs therapy recommended by the 2005 APASL. Patients in group A, without the prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 23 publications
(28 reference statements)
0
31
0
Order By: Relevance
“…The off‐treatment durability in HBeAg‐negative patients seems to be not as good as that in HBeAg‐positive patients. Moreover, there are few head‐to‐head studies comparing the differences between patients with different pretreatment HBeAg status, mainly because of their small sample sizes . On the other hand, although the patients mostly relapse within 3 years, longer follow‐up periods are necessary to identify relapses and to evaluate clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The off‐treatment durability in HBeAg‐negative patients seems to be not as good as that in HBeAg‐positive patients. Moreover, there are few head‐to‐head studies comparing the differences between patients with different pretreatment HBeAg status, mainly because of their small sample sizes . On the other hand, although the patients mostly relapse within 3 years, longer follow‐up periods are necessary to identify relapses and to evaluate clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…IFN and nucleos(t)ide analogue (NAs) CHB treatments have been approved in China, including lamivudine (LAM), adefovir dipivoxil (ADV), entecavir and telbivudine (Pan et al, 2013;Shaw et al, 2006). NA treatment is more convenient than IFN-based therapy, has fewer side effects and more quickly reduces HBV DNA levels.…”
mentioning
confidence: 99%
“…A recent study by Pan et al [16] showed that the cumulative rate of relapse for subjects exposed to prolonged consolidation therapy was significantly lower than for a group who met current standards for cessation of NUC therapy (recommended by the 2005 APASL). This suggests that a sustained response persisting for >48 weeks is a predictive marker for a longer-term sustained response follow- ing discontinuation of NUCs.…”
Section: Discussionmentioning
confidence: 96%